Computer Modelling of the Arc Welding Processes - Dambrauskas, A.; Karaliūnas, B.; Šulskis, D. (Elektronika ir Elektrotechnika, 2004)
The analysis of the welding processes and equipments shows, that existing welding control systems, which were affected by external interferences, does not always fall short of accepted modern standards of formation flanges. The arc welding contour functional and structural schemes are made, there are presented mean equations and transfer function of the closed control system. In most cases the speed of the filler wire are regulated, when arc current and voltage are stabilising according to the quality requirements of the seam. For these purposes in the welding processes control system offer to take aim the regulators with changeable structure and parameters. In this cases, when control object have changeable structure and parameters and it is affected by controlling, but non-controllable interferences, the effectivness of the control system synthesis can be increased using algorithms of the active-passive simplex search. Make up new and perfect a existing model of the welding systems it is expedient to apply adaptive control systems with changeable structure, which reacting to optimization conditions. By using algorithmic synthesis methods of control systems with package Kvazio 1 was made computer modelling of the arc welding process and optained results are analysed and presented. Ill. 7, bibl. 24 (in Lithuanian; summaries in Lithuanian, English and Russian).